Zoo studies : living collections, their animals and visitors / Paul A. Rees. - Rees, Paul A. (Cambridge University Press, 2023)
"This interdisciplinary volume discusses animal housing and welfare, captive breeding, conservation, zoo legislation, and visitor behaviour. This book is an important resource for students studying zoo biology and management, animal welfare, animal behaviour, wildlife conservation and veterinary science, and anyone with a general interest in zoos"-- Provided by publisher.
Keywords: Zoos.; Zoos -- Educational aspects.; Zoos -- Management.; Zoo animals.; Zoo visitors.